Advertising, competition and entry in media industries - Claude Crampes; Carole Haritchabalet; Bruno Jullien (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper presents a model of media competition with free entry when media operators are financed both from advertisers and customers. The relation between advertising receipts and sales receipts, which are both complementary and antagonist, is different if media operators impose a price or a quantity to advertisers. When consumers dislike advertising, media operators are better off setting an advertising price than an advertising quantity. We establish a relationship between the equilibrium levels (advertising and entry) and the advertising technology. In particular, media operators? profit is not affected by the introduction of advertising when they impose advertising quantities and when advertising exhibits constant returns to scale in the audience size. Under constant or increasing returns to scale in the audience size, we find an excessive level of entry and an insufficient level of advertising.
Keywords: L82; L13; 330; media; advertising; free entry; two-sided markets; Werbung; Markteintritt; Werbewirtschaft; Unvollkommener Markt